Investigating the Relationship among Fit Organization, Organization Commitment and Employee’s Intention to Stay: Malaysian Context - Ayesha, Noor; Yuserrie, Zainuddin; Panigrahi, Shrikant; Faridah, Taju Rahim (Sage, 2018)
Retaining employees in the organization has become very crucial especially in tough times. Losing skilled and experienced employees affect the overall productivity, profitability and product quality. While numerous studies have been carried out on this subject and the majority centre on turnover due to organizational approach, only a few studies have been done on intention to stay. Thus, the main purpose of this article is to examine the relationship among fit organization, organizational commitment and employee’s intention to stay in information and communication technology (ICT) industry in Malaysia. Quantitative method with self-administered questionnaire approach is followed targeting information technology (IT) managers of ICT with stratified random sampling of 105 IT professionals of ICT companies in Malaysia, based on the analysis using partial least square structural equation modelling (PLS-SEM) (PLS 3.0) to establish both measurement and structural model. From the empirical findings, it was revealed that there is a strong relationship between organizational commitment and intention to stay. The result also found that religiousness in the employees makes them to stay in the organization. This shows that while remunerations are crucial for the intention of employees, employee’s commitment is much higher than the intention initiatives.